A new guide to immunopharmacology. Issue 12 (December 2018) - Harding, Simon; Faccenda, Elena; Southan, Chris; Maffia, Pasquale; Davies, Jamie
A new guide to immunopharmacology seeks to bring the most valuable pharmacological data into the hands of immunology researchers.